2021
DOI: 10.1056/nejmoa2027030
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial of Fetal Surgery for Severe Left Diaphragmatic Hernia

Abstract: BACKGROUNDObservational studies have shown that fetoscopic endoluminal tracheal occlusion (FETO) has been associated with increased survival among infants with severe pulmonary hypoplasia due to isolated congenital diaphragmatic hernia on the left side, but data from randomized trials are lacking. METHODSIn this open-label trial conducted at centers with experience in FETO and other types of prenatal surgery, we randomly assigned, in a 1:1 ratio, women carrying singleton fetuses with severe isolated congenital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
264
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 267 publications
(269 citation statements)
references
References 48 publications
3
264
1
1
Order By: Relevance
“…Severe Left Diaphragmatic Hernia using fetoscopic endoluminal tracheal occlusion (FETO) for the treatment of severe left diaphragmatic hernia with promising survival outcome. 2 This was a randomized open label trial conducted at specialized centers with experience using FETO and fetal surgery. FETO procedure involves the placement of a balloon in the trachea of the fetus above the carina to occlude the airway and stimulate lung growth including volume and function.…”
Section: Recently Deprest Et Al Published Their Experience the Randomized Trial Of Fetal Surgery Formentioning
confidence: 99%
“…Severe Left Diaphragmatic Hernia using fetoscopic endoluminal tracheal occlusion (FETO) for the treatment of severe left diaphragmatic hernia with promising survival outcome. 2 This was a randomized open label trial conducted at specialized centers with experience using FETO and fetal surgery. FETO procedure involves the placement of a balloon in the trachea of the fetus above the carina to occlude the airway and stimulate lung growth including volume and function.…”
Section: Recently Deprest Et Al Published Their Experience the Randomized Trial Of Fetal Surgery Formentioning
confidence: 99%
“…In addition, pulmonary hypertension (PHT) causes an increase in the right ventricle (RV) after loading, progressively compromising the RV function. Dysfunction and dilation of the RV, in turn, lead to left ventricular (LV) dysfunction, potentially contributing to adverse clinical outcomes [7,65]. Aggarwal et al in fact demonstrated that LV dysfunction was associated with death and negative outcomes, justifying incorporation of echocardiographic indices as prognostic markers of CDH [66].…”
Section: Postnatal Prognostic Factorsmentioning
confidence: 99%
“…Congenital diaphragmatic defects are variable in size encompassing diaphragm agenesis; well-circumscribed defects or "holes"; and, less often, a thinning or undermuscularization of diaphragmatic tissue. Prenatal ultrasound detection is successful in 50% of CDH cases at a mean gestational age of 24 weeks; fetal magnetic resonance imaging (MRI), fetal echocardiography, and three-dimensional ultrasound imaging also play a role in the study of congenital diaphragmatic hernia, including diagnosis, severity stratification, and prognostic prediction [7,8]. The vast majority of neonates with CDH present with cardiorespiratory distress within the first hours or days of life; however, about 5% to 25% of diaphragmatic hernias present beyond the neonatal period (late-presenting CDH), and clinical manifestations may include respiratory or gastrointestinal symptoms, or a combination of both [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, a clinical trial of fetoscopic endoluminal tracheal occlusion (FETO) as a prenatal intervention for CDH is ongoing [7]. FETO has been shown to improve survival rate by increasing lung volume but has the risk of premature delivery due to fetoscopy [5,8]. Therefore, prenatal medical therapies should be explored as alternatives [9].…”
Section: Introductionmentioning
confidence: 99%